Perception and application of flywheel training by professional soccer practitioners - de Keijzer, Kevin; McErlain-Naylor, Stuart A.; E. Brownlee, Thomas; Raya-González, Javier; Beato, Marco (Biology of Sport, 2022)
Growing evidence supports use of eccentric methods for strength development and injury prevention within elite soccer, yet uncertainty remains regarding practitioners’ application of flywheel (isoinertial) methods. The aims of this study were to investigate how the flywheel training literature is perceived and applied by elite soccer practitioners, highlight gaps in knowledge and develop industry-relevant research questions. Fifty-one practitioners completed an electronic questionnaire. Fourteen Likert scale statements were grouped into topics: strength and performance; post-activation performance enhancement and methodological considerations; chronic strength; chronic performance; injury prevention. Three general questions followed, allowing more detail about flywheel training application. A Majority of the participants reported ≥ 2 years’ experience of programming flywheel training. Nearly all participants agreed that familiarisation is needed. Practitioners agree that flywheel training can improve sport performance, strength and likelihood of non-contact injury outcomes. Most practitioners prescribe 2 weekly sessions during pre- and in-season periods. Flywheel sessions mostly consist of squats but a variety of exercises (lunge, hip hinge, and open kinetic chain) are also frequently included. Practitioners are mostly unsure about differences between flywheel and traditional resistance training equipment and outcomes, practicality of flywheel equipment, and evidence-based guidelines. The investigation provides valuable insight into the perspectives and application of flywheel training within elite soccer, highlighting its perceived efficacy for strength and injury prevention.